Interfaces da colonização do oeste catarinense : a antiga fazenda Rodeio Bonito (1920-1954) - Chitolina, Valdirene (2008)
This study investigates the interfaces of colonization in the West of Santa Catarina state, based on the colonizing process of the old farm called Rodeio Bonito, conducted by the subcolonizer group Irmãos Lunardi from 1920 until 1954. It is justified due to advance in regional historiography regarding territorial formation of the cities of Coronel Martins, Entre Rios, Galvão, Ipuaçu, Jupiá, Lajeado Grande, Marema, São Domingos and Xaxim. The leading question of this investigation, based on regional history, deals with the particularities involving the old farm Rodeio Bonito to show identity marks which have transcended the mere geographic and involved culture, economy, politics and historicity of different social groups which have settled in this region due to the colonizing process. For this, documental and bibliographic analyses are used, as well as the oral memories of the caboclos and migrants who took part in the process. It aims at diagnosing territorial disputes; sociocultural organization of the caboclos; the trajectory of “rio-grandenses” migrants to the West of Santa Catarina; the action of colonizers; reconstruction of social, economic, sanitary and domestic environments as well as the transporting system; the operation of the Catholic Church and of the State on the colonizing process. Results show territorial disputes originated the colonization to the West, the posture of State and colonizing companies has been determinant for land appropriation by the migrants, while the caboclos have been licitly or illicitly taken from their areas; the farm Rodeio Bonito, old property of the baroness of Limeira, has been given, by the State, to the colonizer Bertaso, Maia and Co. as payment for the construction of the road between Passo dos Índios and Goio-En; in 1920, this area was sold to subcolonizer group Irmãos Lunardi, which started the controlled colonization, demarcating shares, principally destined to family policulture and wood exploration. Land purchasers were essencialy from the cities of Guaporé, Veranópolis, Antônio Prado, Getúlio Vargas and Fagundes Varela, all in the state of Rio Grande do Sul. Besides these, the study shows the act of the Catholic Church, of religious schools and of the State on the expansion of “brazility” and Romanizing Catholicism in an area which, metaphorically has been transformed into Catholic trench. In a singular way, it also evidences the complex web of interests of local and regional forces in the juridical-administrative evolution of the old farm Rodeio Bonito to the city of Xaxim.